2022
DOI: 10.3390/ani12040491
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Population Structure of Wild Boars (Sus scrofa) in Fukushima Prefecture

Abstract: We aimed to reveal the dispersal and gene flow of the local wild boar (Sus scrofa) population and find their genetic boundary in Fukushima Prefecture. After the nuclear incident in 2011, the land was considered a difficult-to-return zone, and the increase in the number of wild boars was pronounced. To provide an effective management strategy for the wild boar population, we used multiplexed inter-simple sequence repeat genotyping by sequencing (MIG-seq) and clarified the genetic structure of wild boars. We obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Based on the whole-genome sequencing data, this study conducted an overall evaluation of the genetic diversity and population structure of LUX, which is helpful to accurately understand the genetic diversity and breeding situation of current LUX. Compared with microsatellite markers, genome-wide SNP markers can more objectively reflect genetic differences between individuals and are increasingly used to analyze the genetic diversity of populations [ 32 ]. Genetic diversity is a key factor for population survival and evolution, and based on the analysis of the whole genome sequencing results, we can develop a rational breeding program to reduce inbreeding and maintain the genetic diversity of LUX [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the whole-genome sequencing data, this study conducted an overall evaluation of the genetic diversity and population structure of LUX, which is helpful to accurately understand the genetic diversity and breeding situation of current LUX. Compared with microsatellite markers, genome-wide SNP markers can more objectively reflect genetic differences between individuals and are increasingly used to analyze the genetic diversity of populations [ 32 ]. Genetic diversity is a key factor for population survival and evolution, and based on the analysis of the whole genome sequencing results, we can develop a rational breeding program to reduce inbreeding and maintain the genetic diversity of LUX [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found that dpMIG-seq libraries could be constructed using DNA extracted via a method lacking a purification step (Jia et al ., 2021), indicating that dpMIG-seq does not require high-quality DNA, an advantage of MIG-seq originally described by Suyama and Matsuki (2015). MIG-seq has been used in many ecological and taxonomic studies since its development (Cho et al ., 2021; Hirota et al ., 2021, 2022; Hoshino et al ., 2021; Nakajima et al ., 2021; van Ngoc et al ., 2021; Saito et al ., 2022; Toji et al ., 2022; Yahara et al ., 2021a, 2021b), although <1,000 SNPs were available in some studies (Table S10). As a novel method, dpMIG-seq may be useful as an alternative to conventional MIG-seq in future ecological and taxonomic studies that require an increased number of markers when clonal identification or species with small genomes are the target of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…development (Cho et al, 2021;Hirota et al, 2021Hirota et al, , 2022Hoshino et al, 2021;Nakajima et al, 2021;van Ngoc et al, 2021;Saito et al, 2022;Toji et al, 2022;Yahara et al, 2021aYahara et al, , 2021b, although <1,000 SNPs were available in some studies (Table S10). As a novel method, dpMIG-seq may be useful as an alternative to conventional MIG-seq in future ecological and taxonomic studies that require an increased number of markers when clonal identification or species with small genomes are the target of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although a previous microsatellite analysis also detected two ancestral clusters of many Japanese wild boar individuals collected over multiple years from an area larger than the present study area in the Hokuriku region (Yamazaki et al, 2016), the results of the present study confirm that these clusters were present from the beginning of the expansion period. Based on an analysis of single nucleotide polymorphisms (SNPs), Saito et al (2022) indicated the possibility of dispersal of Japanese wild boars from neighboring prefectures in the western region of Fukushima Prefecture, Japan. In Belgium, the gene pool of wild boar individuals that had immigrated and expanded from neighboring areas since around 2006 was reported to have two nearly independent genetic compositions at the beginning of the study, but with the passage of time, the genetic compositions had become more admixed (Rutten et al, 2019).…”
Section: Genetic Features Of Japanese Wild Boar In the Hokuriku Regionmentioning
confidence: 99%
“…In an effort to reduce damage by Japanese wild boar and to guide management of its population, many researchers have investigated landscape conditions that affect wild boar occurrence, the extent of wild boar damage to agricultural crops, and the expansion of its distribution range (Ueda and Jiang, 2004; Nomoto et al, 2010; Saito et al, 2012; Shimizu et al, 2013; Yokoyama et al, 2020; Ohnishi et al, 2022). Concurrently, phylogeographic and population genetic analyses have been conducted to estimate Japanese wild boar dispersal pathways, with mountains, such as the Japanese Alps, and rivers having been reported to be geographic barriers to their dispersal (Watanobe et al, 2003; Saito et al, 2022).…”
Section: Introductionmentioning
confidence: 99%